Burnout in teachers: predictive role of emotional intelligence and humor - Martínez-Álvarez, Isabel (2024)
Introduction: high levels of stress can cause burnout with negative effects for the person, being more pronounced and frequent in work environments such as teachers. Emotional intelligence and humor style are related to its appearance, duration and intensity. Objective: to analyze this syndrome in teachers, as well as the degree of prediction that emotional intelligence and humor styles have on it. Method: Cross-sectional predictive design. The sample consists of 196 teachers. Results: a relationship was found between aspects of emotional intelligence and humor styles with burnout. The regression analysis showed that emotional regulation partly predict professional burnout and that the evaluation of one’s own emotions and affiliative mood explain part of the student-related burnout. Discussion: Emotional intelligence, especially that related to the use and regulation of emotions, and adaptive humor style are negatively related and predict less burnout in teachers, so they could benefit from intelligence training. emotion as part of prevention and treatment strategies.